A poética do silêncio em Vidas secas e a Hora da estrela - Silva, Carlos Augusto Moraes (2013)
By electing the works Vidas Secas (1938) and The Hour of the Star (1977) as a corpus to this analysis, this paper aims to show how the silence introduced on speech characters and on narratives architecture is configured as a mechanism for expression. To achieve these goals, the book Linguagem e Silêncio: ensaios sobre a crise da palavra (1988), of George Steiner and the essay A Estética do Silêncio (1987), of Susan Sontag will be used as theoretical-critical aspects. Moreover, it is also intended to question the artistic resourcefulness of Graciliano Ramos and Clarice Lispector, authors who had written books as a way to protest against the institutionalized literary language. Furthermore, Steiner and Sontag establish a scathing critique about the verbosity , trivia masquerading as erudition that threaten the power of communication and expression in contemporary art and cast a troubling question for the critic and literary historiography: Has our civilization lost the right to that luxury we call Literature, because of inhumanity that was practiced and covered up? In this context, the artist inquires: Where is the silence necessary to hear the metamorphosis? When they produced the works mentioned above, Ramos and Lispector proved that the Literature is still possible, even before the feeling about the language death. So, they prepare lean texts, without decorations or ornaments, exposing the fragility of Fabiano and Macabéa s silence, not only about those who have been silenced throughout history, but also from people who believed that they had their last word in comfort.